Anti-erosion high-chromizing fused cast zirconia corundum ceramic and preparation method thereof

Through the preparation of high-chromium melt-cast zirconium corundum ceramics, the problem of insufficient corrosion resistance in nuclear waste treatment by using melt-casting and casting technology and ultrasonic nano-spraying technology is solved, and the material's efficient corrosion resistance and high-temperature resistance is improved , extends service life.

CN119263789APending Publication Date: 2025-01-07LUOYANG INST OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411337646.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing high-chromium sintered bricks have poor corrosion resistance in nuclear waste glass curing continuous combustion furnaces, short service life, insufficient grain development, poor material combination, and high porosity, which cannot effectively resist high temperature and chemical corrosion.

Method used

Using high-chromium melted cast zirconium corundum ceramics, the reasonable ratio of electromelted chromium oxide sand, zirconium corundum sand, alumina powder, yttrium oxide powder and polyamide resin, combined with melt casting technology and ultrasonic nanospraying technology, the excellent resistance is prepared. Materials with erosion properties improve the density and high temperature resistance of the material.

Benefits of technology

It significantly improves the corrosion resistance and high temperature resistance of the material, extends the service life, is suitable for nuclear waste treatment and boron glass kilns and enhances the heat resistance and corrosion resistance of the furnace.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The preparation method mainly comprises the following steps: preparing the corrosion-resistant high-chromium fused cast zirconia corundum ceramic from electrically-fused chromic oxide sand, fused zirconia corundum sand, alumina powder, yttrium oxide powder and polyamide resin with excellent performance according to a certain proportion by adopting a fusion casting process; the high-chromium fused cast zirconia corundum ceramic with excellent corrosion resistance is prepared through the procedures of burdening, preheating in a heat preservation box, melting in an electric furnace, casting molding, heat preservation annealing, cold machining, coating spraying, drying and curing and the like, and the preparation cost is low; the prepared high-chromium fused cast zirconia corundum ceramic material has the characteristics of low melt index, low residual quartz content, low expansion rate, excellent erosion resistance, corrosion resistance, high temperature resistance and the like, is applied to a nuclear waste glass curing continuous combustion furnace, and can also be applied to medium-high boron glass kilns, glass fiber kilns and the like; the heat resistance and the corrosion resistance of the smelting furnace are effectively enhanced, the service life is prolonged, and the method has important application significance in the fields of nuclear waste treatment, high borosilicate glass smelting furnaces and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a corrosion-resistant high-chromium fused-cast zirconium corundum ceramic and a preparation method thereof. Background Art

[0002] Nuclear waste vitrification is a treatment method that mixes high-level radioactive waste liquid with glass raw materials to melt, and then cools to form a glass body that can contain radioactive substances for a long time. This technology is carried out at a temperature of 1100°C or higher, and the formed glass body needs to be able to contain radioactive substances for more than a thousand years. In a broad sense, nuclear waste includes wastewater, waste gas and spent fuel generated by the normal operation of nuclear power plants. These wastes are divided into high-level waste (HLW), medium-level waste (MLW) and low-level waste (LLW) according to their radioactivity levels. In a narrow sense, it refers specifically to the spent fuel left over from burning in nuclear power plants.

[0003] During the process of nuclear waste glass solidification, the lining refractory materials of the continuous combustion furnace need not only to have excellent high temperature resistance and corrosion resistance, but also to be chemically and physically stable to cope with extreme operating environments and the corrosiveness of nuclear waste. The requirements for high temperature resistance and corrosion resistance of refractory bricks are much higher than those of ordinary refractory bricks. Sintered high-chromium refractory bricks are often used, which are pressed and formed by friction brick presses and fired in high-temperature kilns at 1600-1800℃. Sintered high-chromium bricks have the advantages of high strength at room temperature and high temperature, good wear resistance, high refractoriness, and good high-temperature volume stability. They can also protect facilities from high temperature and chemical corrosion, and control the nuclear reaction rate by absorbing neutrons to improve overall safety. The mechanical strength and thermal shock resistance of these materials ensure the stability and reliability of the structure, while their corrosion resistance ensures the integrity of the structure when in long-term contact with radioactive substances. However, the high-chrome bricks prepared by the sintering process have shortcomings such as insufficient grain development, poor physical bonding, and high porosity, which lead to unsatisfactory corrosion resistance and short service life of sintered high-chrome bricks in the harsh environment of nuclear waste glass solidification continuous combustion furnaces.

[0004] Zirconia corundum bricks have excellent performance, with the advantages of dense structure, strong corrosion resistance, and little pollution to glass liquid, which makes them occupy an important position in the field of refractory materials and are widely used in various industries that require high-performance refractory materials, especially the glass industry; and chromium oxide has the best corrosion resistance in the oxide material system, and fused-cast refractory materials have the advantages of dense structure, low porosity, crystals clamped together as intercrystalline bonding, strong corrosion resistance and low creep rate. Therefore, combining the above advantages, developing high-chromium fused-cast zirconium corundum ceramic refractory materials with extremely excellent corrosion resistance, which can withstand the erosion of borosilicate glass and highly radioactive waste liquid containing a large amount of heavy metals, can meet the service requirements of the lining of continuous combustion furnaces for nuclear waste treatment, and is an important part of solving the problem of nuclear waste treatment. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a corrosion-resistant high-chromium fused-cast zirconium corundum ceramic and a preparation method thereof. The method mainly comprises the following steps: mixing excellent fused chromium oxide sand, zirconium corundum sand, alumina powder, yttrium oxide powder and polyamide resin in a certain proportion, adopting a melting and casting process, and undergoing the steps of batching, preheating in an insulation box, melting in an electric furnace, casting, insulation annealing, cold processing, coating spraying, drying and curing, so as to prepare the high-chromium fused-cast zirconium corundum ceramic with excellent corrosion resistance, thereby improving the service life of the lining of a continuous combustion furnace for nuclear waste treatment.

[0006] The technical scheme adopted by the present invention is: an anti-corrosion high-chromium fused-cast zirconium corundum ceramic, which is composed of the following raw material components and the weight proportions added: 80-90 parts of fused chromium oxide sand, 5-15 parts of zirconium corundum sand, 5-10 parts of aluminum oxide powder, 1-2 parts of yttrium oxide powder and 1-3 parts of polyamide resin.

[0007] The purity of the fused chromium oxide sand is greater than 95wt%, and the proportions of 200 mesh, 600 mesh and 1000 mesh are 2:2:3. This ratio can reduce pores while ensuring the strength and shape stability of the bricks, and promote the densification of the material during the sintering process.

[0008] The purity of the zirconium corundum sand is greater than 95wt%, and the particle sizes of 200 mesh, 600 mesh, 1000 mesh and 2000 mesh account for 2:3:3:1. Reasonable proportioning can effectively reduce the porosity of the final product and increase the density of the product.

[0009] The purity of the aluminum oxide powder is greater than 95 wt %, and the particle size is less than or equal to 5 μm.

[0010] The purity of the yttrium oxide powder is greater than 98 wt %, and the particle size is less than or equal to 3 μm.

[0011] The polyamide resin has a purity of >98 wt % and a particle size of ≤120 μm.

[0012] A method for preparing corrosion-resistant high-chromium fused-cast zirconium corundum ceramics comprises the following steps: Step 1: batching: add the raw materials into the mixer according to the batching ratio and mix until fully mixed and uniform to obtain the batching material; Step 2: Preheating in an insulated box: Place the batch material described in step 1 in an insulated box for preheating, and keep the batch material temperature at 350°C; Step 3, melting in an electric furnace: add the batch material into an automatically controlled electric arc furnace with a three-phase arc voltage of 200-260V. After melting for 80-90 minutes, turn off the power to stop melting, blow oxygen for 3 minutes with an oxygen flow rate of 15m³ / h, and the melted casting liquid is obtained. During the melting process, the oxygen blowing process should be carried out simultaneously to stir the melt. At the same time, hot oxygen can also keep the melt at a temperature of 0.4-1.0MPa. Step 4: Casting: Inject the casting liquid into the product mold, the casting temperature is 2050-2300°C, and the casting speed is 120-1050kg / min; Step 5: Insulation annealing: put the cast bricks into the tunnel kiln, and cool down at a rate of 0.05-0.10℃ / kg·h; Step 6: Cold processing: Diamond grinding is performed according to the appearance, size and surface accuracy of the brick; Step 7, coating spraying: before spraying, use warm water to clean by spraying or immersion, and use ultrasonic high-precision nano-spraying technology to spray Ni-Fe alloy coating, which shows amorphous characteristics without component segregation and second phase precipitation, so that high chromium fused-cast zirconium corundum ceramics have better corrosion resistance; Step 8, drying and curing: placing the high chromium-coated fused-cast zirconium corundum ceramic after spray coating in an oven to dry and cure the coating; the formed Ni-Fe alloy coating has 78-80% Ni as the matrix, 18-20% Fe as the main added element, and contains trace amounts of Cr, Cu, and Si elements.

[0013] The present invention increases the chromium content and adds a small amount of zirconium corundum. The increase in the chromium content and the interlocking structure of zirconium oxide and corundum phases can generate an intermetallic bond zirconium-chromium compound, which has excellent high temperature resistance and corrosion resistance, inhibits the penetration of the glass phase, and improves the erosion resistance of the refractory material; a small amount of yttrium oxide is added to form a zirconium bonding phase with zirconium oxide, changes the phase transition temperature of zirconium oxide to keep a stable cubic crystal structure, and improves high temperature resistance.

[0014] The introduction of yttrium oxide into the raw material of the present invention can make a part of Y 3+ Replace Al 3+ , so that yttrium oxide is dissolved in the alumina lattice, causing the grains to grow to a certain extent, but another part of the yttrium oxide is free between the alumina grains, forming a second phase yttrium aluminum garnet with alumina, inhibiting its sintering, playing a role in enhancing the complementary phase, affecting the organizational structure and mechanical properties of materials such as alumina, especially improving the fracture toughness and strength, and increasing the service life of refractory materials.

[0015] In step 2 of the present invention, a heat preservation box is used for preheating to keep the batch temperature at 350° C., thereby improving the reactivity of the material and ensuring that the melting and reaction processes are more efficient.

[0016] In the third step of the present invention, the process of "auxiliary oxygen blowing" is adopted in the electric furnace melting process. For the oxidized molten products, in order to meet the requirements of the melt on the degree of oxidation, reduce the carbon pollution to a sufficiently low level, and minimize the foaming tendency of the products, oxygen blowing is carried out during the melting process of the batch materials and after the melting and refining. In this way, the carbon pollution in the melt can be removed, and the stirring effect of the melt tumbling up and down during oxygen blowing can be utilized. At the same time, the hot oxygen can also keep the temperature of the melt, homogenize the temperature and composition of the melt in the furnace, and at the same time, the low-valent oxides in the melt in the furnace can be converted into high-valent oxides; improve the properties of the glass phase in the crystal composition of the product and the composition ratio and structure of the main crystal phase, so that the glass phase seepage temperature of the product is increased, the seepage is reduced, and the crack tendency is reduced.

[0017] For the coating spraying of step seven, ultrasonic high-precision nano-spraying technology is used, which is a spraying method based on ultrasonic atomization nozzle technology. The Ni-Fe-containing liquid coating is first decomposed into a uniform fine mist of micron-level or even nano-level droplets by an ultrasonic atomization device, and then evenly coated on the surface of high-chromium fused-cast zirconium corundum ceramics through a certain amount of carrier gas, thereby forming a Ni-Fe-containing alloy coating; ultrasonic atomization spraying can achieve better uniformity, thinner coating thickness, and higher precision, can significantly reduce paint splashing during the spraying process, accurately spray, and have good coating homogeneity, thereby enhancing the corrosion resistance of high-chromium fused-cast zirconium corundum ceramics.

[0018] The beneficial effects of the present invention are: The invention adopts cheap and easily available raw materials, has low preparation cost and relatively simple preparation process. The high-chromium fused-cast zirconium corundum ceramic material prepared by the invention has the characteristics of low melting index, low residual quartz content, low expansion rate, excellent erosion resistance, corrosion resistance and high temperature resistance, etc., and is mainly used in nuclear waste glass solidification continuous combustion furnaces, and can also be used in medium and high boron glass kilns, glass fiber kilns, etc., effectively enhancing the heat resistance and corrosion resistance of the furnace and improving the service life, and has important application significance in the fields of nuclear waste treatment, high borosilicate glass melting furnaces, etc. DETAILED DESCRIPTION

[0019] The present invention will be further described in detail below with reference to specific embodiments. Example 1

[0020] The invention discloses a corrosion-resistant high-chromium fused-cast zirconium corundum ceramic, whose raw material components and added weight portions are: 85 parts of fused chromium oxide sand, 7 parts of zirconium corundum sand, 5 parts of aluminum oxide powder, 1 part of yttrium oxide powder and 2 parts of polyamide resin.

[0021] A method for preparing corrosion-resistant high-chromium fused-cast zirconium corundum ceramics comprises the following steps: Step 1, batching: add the raw materials into the mixer according to the above batching ratio and mix until fully mixed to obtain the batching material; Step 2: Preheating in an incubator: Place the batch prepared in step 1 in an incubator for preheating to maintain the batch temperature at 350°C; Step 3, melting in an electric furnace: add the batch material into an automatically controlled electric arc furnace with a three-phase arc voltage of 260V. After melting for 85 minutes, turn off the power to stop melting, blow oxygen for 3 minutes with an oxygen flow rate of 15m³ / h, and the melted casting liquid is obtained. The oxygen blowing process should be carried out simultaneously during the melting process with an oxygen pressure of 0.8MPa. Step 4: Casting: Inject the casting liquid into the product mold at a casting temperature of 2190°C and a casting speed of 530kg / min; Step 5: Insulation annealing: put the cast bricks into the tunnel kiln, and cool down at a rate of 0.06℃ / kg·h; Step 6: Cold processing: Diamond grinding is performed according to the appearance, size and surface accuracy of the brick; Step 7: Coating spraying: Before spraying, use warm water to clean by spraying or immersion, and use ultrasonic high-precision nano-spraying technology to spray Ni-Fe alloy coating; Step 8: Drying and curing: placing the high-chromium fused-cast zirconium corundum ceramic after spraying the coating in an oven to dry and cure the coating. Example 2

[0022] The invention discloses a corrosion-resistant high-chromium fused-cast zirconium corundum ceramic, whose raw material components and added weight portions are: 82 parts of fused chromium oxide sand, 8 parts of zirconium corundum sand, 7 parts of aluminum oxide powder, 1 part of yttrium oxide powder and 2 parts of polyamide resin.

[0023] A method for preparing corrosion-resistant high-chromium fused-cast zirconium corundum ceramics comprises the following steps: Step 1, batching: add the raw materials into the mixer according to the above batching ratio and mix until fully mixed to obtain the batching material; Step 2: Preheating in an incubator: Place the batch prepared in step 1 in an incubator for preheating to maintain the batch temperature at 350°C; Step 3, melting in an electric furnace: add the batch material into an automatically controlled electric arc furnace with a three-phase arc voltage of 216V. After melting for 80 minutes, turn off the power to stop melting, blow oxygen for 3 minutes with an oxygen flow rate of 15m³ / h, and the melted casting liquid is obtained. During the melting process, the oxygen blowing process should be carried out at the same time to make the oxygen pressure 0.7MPa. Step 4: Casting: Inject the casting liquid into the product mold at a casting temperature of 2130°C and a casting speed of 370kg / min; Step 5: Insulation annealing: put the cast bricks into the tunnel kiln, and cool down at a rate of 0.09℃ / kg·h; Step 6: Cold processing: Diamond grinding is performed according to the appearance, size and surface accuracy of the brick; Step 7: Coating spraying: Before spraying, use warm water to clean by spraying or immersion, and use ultrasonic high-precision nano-spraying technology to spray Ni-Fe alloy coating; Step 8: Drying and curing: placing the high-chromium fused-cast zirconium corundum ceramic after spraying the coating in an oven to dry and cure the coating. Example 3

[0024] The invention discloses a corrosion-resistant high-chromium fused-cast zirconium corundum ceramic, whose raw material components and added weight portions are: 83 parts of fused chromium oxide sand, 8 parts of zirconium corundum sand, 6 parts of aluminum oxide powder, 1 part of yttrium oxide powder and 2 parts of polyamide resin.

[0025] A method for preparing corrosion-resistant high-chromium fused-cast zirconium corundum ceramics comprises the following steps: Step 1, batching: add the raw materials into the mixer according to the above batching ratio and mix until fully mixed to obtain the batching material; Step 2: Preheating in an incubator: Place the batch prepared in step 1 in an incubator for preheating to maintain the batch temperature at 350°C; Step 3, electric furnace melting: add the batch material into an automatically controlled electric arc furnace with a three-phase arc voltage of 210V. After melting for 80 minutes, turn off the power to stop melting, blow oxygen for 3 minutes with an oxygen flow rate of 15m³ / h, and the melted casting liquid is obtained. The oxygen blowing process should be carried out simultaneously during the melting process with an oxygen pressure of 0.6MPa. Step 4: Casting: Inject the casting liquid into the product mold at a casting temperature of 2210°C and a casting speed of 670kg / min; Step 5: Insulation annealing: put the cast bricks into the tunnel kiln, and cool down at a rate of 0.05℃ / kg·h; Step 6: Cold processing: Diamond grinding is performed according to the appearance, size and surface accuracy of the brick; Step 7: Coating spraying: Before spraying, use warm water to clean by spraying or immersion, and use ultrasonic high-precision nano-spraying technology to spray Ni-Fe alloy coating; Step 8: Drying and curing: placing the high-chromium fused-cast zirconium corundum ceramic after spraying the coating in an oven to dry and cure the coating. Example 4

[0026] The invention discloses a corrosion-resistant high-chromium fused-cast zirconium corundum ceramic, whose raw material components and added weight portions are: 86 parts of fused chromium oxide sand, 6 parts of zirconium corundum sand, 5 parts of aluminum oxide powder, 1 part of yttrium oxide powder and 2 parts of polyamide resin.

[0027] A method for preparing corrosion-resistant high-chromium fused-cast zirconium corundum ceramics comprises the following steps: Step 1, batching: add the raw materials into the mixer according to the above batching ratio and mix until fully mixed to obtain the batching material; Step 2: Preheating in an incubator: Place the batch prepared in step 1 in an incubator for preheating to maintain the batch temperature at 350°C; Step 3, melting in an electric furnace: add the batch material into an automatically controlled electric arc furnace with a three-phase arc voltage of 235V. After melting for 90 minutes, turn off the power to stop melting, blow oxygen for 3 minutes with an oxygen flow rate of 15m³ / h, and the melted casting liquid is obtained. During the melting process, the oxygen blowing process should be carried out at the same time with an oxygen pressure of 0.6MPa. Step 4: Casting: Inject the casting liquid into the product mold at a casting temperature of 2190°C and a casting speed of 420kg / min; Step 5: Insulation annealing: put the cast bricks into the tunnel kiln, and cool down at a rate of 0.07℃ / kg·h; Step 6: Cold processing: Diamond grinding is performed according to the appearance, size and surface accuracy of the brick; Step 7: Coating spraying: Before spraying, use warm water to clean by spraying or immersion, and use ultrasonic high-precision nano-spraying technology to spray Ni-Fe alloy coating; Step 8: Drying and curing: placing the high-chromium fused-cast zirconium corundum ceramic after spraying the coating in an oven to dry and cure the coating. Example 4

[0028] The invention discloses a corrosion-resistant high-chromium fused-cast zirconium corundum ceramic, whose raw material components and added weight portions are: 80 parts of fused chromium oxide sand, 12 parts of zirconium corundum sand, 5 parts of aluminum oxide powder, 1 part of yttrium oxide powder and 2 parts of polyamide resin.

[0029] A method for preparing corrosion-resistant high-chromium fused-cast zirconium corundum ceramics comprises the following steps: Step 1, batching: add the raw materials into the mixer according to the above batching ratio and mix until fully mixed to obtain the batching material; Step 2: Preheating in an incubator: Place the batch prepared in step 1 in an incubator for preheating to maintain the batch temperature at 350°C; Step 3, melting in an electric furnace: add the batch material into an automatically controlled electric arc furnace with a three-phase arc voltage of 220V. After melting for 85 minutes, turn off the power to stop melting, blow oxygen for 3 minutes with an oxygen flow rate of 15m³ / h, and the melted casting liquid is obtained. The oxygen blowing process should be carried out simultaneously during the melting process with an oxygen pressure of 0.8MPa. Step 4: Casting: Inject the casting liquid into the product mold at a casting temperature of 2250°C and a casting speed of 1000kg / min; Step 5: Insulation annealing: put the cast bricks into the tunnel kiln, and cool down at a rate of 0.09℃ / kg·h; Step 6: Cold processing: Diamond grinding is performed according to the appearance, size and surface accuracy of the brick; Step 7: Coating spraying: Before spraying, use warm water to clean by spraying or immersion, and use ultrasonic high-precision nano-spraying technology to spray Ni-Fe alloy coating; Step 8: Drying and curing: placing the high-chromium fused-cast zirconium corundum ceramic after spraying the coating in an oven to dry and cure the coating.

[0030] The high chromium fused-cast zirconium corundum bricks prepared in Examples 1-5 were sampled and tested, and the main chemical composition and physical properties test results were as follows: Table 1 Physical and chemical properties of high chromium melt-cast zirconium corundum ceramics

[0031] The physical and chemical properties of the high-chromium fused-cast zirconium corundum ceramics prepared in the above Examples 1 to 5 are shown in Table 1. It can be seen from Table 1 that the high-chromium fused-cast zirconium corundum ceramics of the present invention have excellent properties, low apparent porosity, small penetration depth, high compressive strength, excellent corrosion resistance, and can effectively improve the performance of the kiln.

[0032] The parts of the present invention that are not described in detail are prior art. The above embodiments will help relevant persons in the art to further understand the present invention, but do not limit the present invention in any form. Without departing from the scope of the present invention defined by the attached claims, various changes in form, details or equivalents made using the present invention are all within the protection scope of the present invention.

Claims

1. A corrosion-resistant high-chromium fused-cast zirconium corundum ceramic, characterized in that: The invention is composed of the following raw material components and the added weight proportions: 80-90 parts of fused chromium oxide sand, 5-15 parts of zirconium corundum sand, 5-10 parts of aluminum oxide powder, 1-2 parts of yttrium oxide powder and 1-3 parts of polyamide resin.

2. The corrosion-resistant high-chromium fused-cast zirconium corundum ceramic according to claim 1, characterized in that: The purity of fused chromium oxide sand is >95wt%, and the proportions of 200 mesh, 600 mesh and 1000 mesh are 2:2:

3.

3. The corrosion-resistant high-chromium fused-cast zirconium corundum ceramic according to claim 1, characterized in that: The purity of zirconium corundum sand is >95wt%, and the proportions of particle sizes of 200 mesh, 600 mesh, 1000 mesh and 2000 mesh are 2:3:3:

1.

4. The corrosion-resistant high-chromium fused-cast zirconium corundum ceramic according to claim 1, characterized in that: The purity of alumina powder is >95 wt %, and the particle size is ≤5μm.

5. The corrosion-resistant high-chromium fused-cast zirconium corundum ceramic according to claim 1, characterized in that: The purity of yttrium oxide powder is greater than 98 wt %, and the particle size is ≤3 μm.

6. The corrosion-resistant high-chromium fused-cast zirconium corundum ceramic according to claim 1, characterized in that: The purity of the polyamide resin is greater than 98 wt %, and the particle size is ≤120 μm.

7. A method for preparing the corrosion-resistant high-chromium fused-cast zirconium corundum ceramic according to claim 1, characterized in that: The following steps are involved: Step 1: batching: add the raw materials into the mixer according to the batching ratio and mix until fully mixed and uniform to obtain the batching material; Step 2: Preheating in an insulated box: Place the batch material described in step 1 in an insulated box for preheating, and keep the batch material temperature at 350°C; Step 3, melting in an electric furnace: add the batch material into an automatically controlled electric arc furnace with a three-phase arc voltage of 200-260V. After melting for 80-90 minutes, turn off the power to stop melting, blow oxygen for 3 minutes with an oxygen flow rate of 15m³ / h, and the melted casting liquid is obtained. During the melting process, oxygen blowing should be carried out simultaneously to stir the melt with an oxygen pressure of 0.4-1.0MPa. Step 4: Casting: Inject the casting liquid into the product mold, the casting temperature is 2050-2300°C, and the casting speed is 120-1050kg / min; Step 5: Insulation annealing: put the cast bricks into the tunnel kiln, and cool down at a rate of 0.05-0.10℃ / kg·h; Step 6: Cold processing: Diamond grinding is performed according to the appearance, size and surface accuracy of the brick; Step 7: Coating spraying: Before spraying, use warm water to clean by spraying or immersion, and use ultrasonic high-precision nano-spraying technology to spray Ni-Fe alloy coating; Step 8, drying and curing: the high chromium-coated fused-cast zirconium corundum ceramic after spray coating is placed in an oven for drying and curing of the coating; the formed alloy coating has 78-80% Ni as the matrix, 18-20% Fe as the main added element, and contains trace amounts of Cr, Cu, and Si elements.

Citation Information

Patent Citations

  • Preparation method of zircon corundum brick containing chromic oxide

    CN104446564A

  • Chromium-zirconium compound brick and preparation technology thereof

    CN105669171A

  • Preparation method of low-exudation fused zirconia corundum brick added with yttrium oxide

    CN112979292A

  • Casting high-chromium refractory brick

    CN115043660A

  • Alloy powder for thermally spraying amorphous wear-resistant coating and preparation method

    CN117816958A